Development of a parametric model order reduction method for laminated composite structures. (1st July 2020) - Bova, Walter; Lappano, Ettore; Catera, Piervincenzo G.; Mundo, Domenico
Abstract: This paper presents a parametric model order reduction (PMOR) method for laminated composite structures. The approach is applied to a lattice structure made of carbon fibre reinforced polymer (CFRP) beams. The global reduced order basis (ROB) used to apply the reduction is calculated with two different methods: the Modal-SVD (singular value decomposition) and the proper orthogonal decomposition (POD). Then, the reduced model is obtained by a Galerkin projection. The parametrization is carried out for the angle between the layers of the structure and for the thickness of the structure. The results show how the use of the reduced basis (RB) method to create reduced parametric models of composite structures is an efficient approach that allows to decrease the computational cost of the simulation.